1997
DOI: 10.1088/0026-1394/34/5/8
|View full text |Cite
|
Sign up to set email alerts
|

On the International Temperature Scale of 1990 (ITS-90). Part I: Some definitions

Abstract: In this paper, we specify the purpose of an international temperature scale and present some definitions that are basic to the International Temperature Scale of 1990. These definitions include those for non-uniqueness and for the temperature fixed points underlying the scale. Three types of non-uniqueness are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 3 publications
0
79
0
Order By: Relevance
“…One of the mathematical ambiguities of the ITS-90 is the Type 3 non-uniqueness of calibrated platinum resistance thermometers: temperature measurements made with several different thermometers agree with one another, by definition, at the ITS-90 defining fixed points, but disagree with one another at temperatures between the defining fixed points [4,5]. Expressions for the uncertainty due to Type 3 non-uniqueness are derived in table 7.2 of reference [24] by fitting the temperature-dependent standard deviation of a set of many thermometers from the comprehensive experimental data of reference [5] in temperature intervals between 24 K and 273.16 K. In the temperature range 83.8058 K to 234.3156 K, the uncertainty due to Type 3 non-uniqueness is estimated as [24] δT non−uniqueness = 2.…”
Section: Csprt Type 3 Non-uniquenessmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the mathematical ambiguities of the ITS-90 is the Type 3 non-uniqueness of calibrated platinum resistance thermometers: temperature measurements made with several different thermometers agree with one another, by definition, at the ITS-90 defining fixed points, but disagree with one another at temperatures between the defining fixed points [4,5]. Expressions for the uncertainty due to Type 3 non-uniqueness are derived in table 7.2 of reference [24] by fitting the temperature-dependent standard deviation of a set of many thermometers from the comprehensive experimental data of reference [5] in temperature intervals between 24 K and 273.16 K. In the temperature range 83.8058 K to 234.3156 K, the uncertainty due to Type 3 non-uniqueness is estimated as [24] δT non−uniqueness = 2.…”
Section: Csprt Type 3 Non-uniquenessmentioning
confidence: 99%
“…Improving the measurement and understanding of these secondary reference points remains a field of active research: for example, updated measurements have shown that the triple point of xenon, currently listed as a "first quality" secondary reference point [2] is suitable for inclusion as a defining fixed point of the next ITS revision [3] as a means of reducing the severity of the ITS-90 non-uniqueness problem between the triple point of argon and the triple point of water [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Differences of less than 10 mK have been found between 5N and 6N Ag samples. A detailed analysis with references on the influence of impurities can also be found in [13,19,20].…”
Section: Impuritiesmentioning
confidence: 99%
“…The review protocol provides three-tier algorithms for determining whether no review, an RMO-level review, or a CCT WG8 review is necessary. The cutoff values (U comb ) used in the algorithms were determined from the statistical derivation of 25th and 75th percentile values of the combined CCT K3 and CCT K4 uncertainties and Type I and Type III non-uniqueness values [13]. The Type I and Type III non-uniqueness values were derived from several published and unpublished literature sources.…”
Section: Its-90 Subrange Cmc Review Protocolmentioning
confidence: 99%